Molecular Characterization and Serology of Leptospira kirschneri (Serogroup Grippotyphosa) Isolated from Urine of a Mare Post-Abortion in Brazil - Hamond, C. (2016)
Universidade Federal Fluminense. Department of Microbiology and Parasitology. Laboratory of Veterinary Bacteriology. Niterói, RJ, Brasil.